Why European Banks Adjust their Dividend Payouts? - Belloni, Marco (IMF Working Papers; Working Paper, 2022)
Using a panel data approach for two samples of listed and unlisted European banks, this paper provides evidence that, over a decade and a half preceding the pandemic, bank dividend payouts were adjusted in line with the motivations found in the literature. Banks change their dividend payouts because they would like to signal good profitability to shareholders to address information asymmetry, or use dividends to mitigate the agency costs, or could come under pressure from prudential supervisors and regulators to retain earnings. Banks are found not to discount expectations about future economic conditions or their own profitability when making payouts. Simulations show that, in the absence of supervisory sector-wide recommendations to suspend dividend payouts, banks would likely have reduced the payouts only slightly in the first year of the pandemic.